2019
DOI: 10.1128/mcb.00037-19
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide CRISPR Screen Reveals Autophagy Disruption as the Convergence Mechanism That Regulates the NRF2 Transcription Factor

Abstract: The nuclear factor (erythroid 2)-like 2 (NRF2 or NFE2L2) transcription factor regulates the expression of many genes that are critical in maintaining cellular homeostasis. Its deregulation has been implicated in many diseases, including cancer and metabolic and neurodegenerative diseases. While several mechanisms by which NRF2 can be activated have gradually been identified over time, a more complete regulatory network of NRF2 is still lacking. Here we show through a genome-wide clustered regularly interspaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…Other reports contradict the induction of NRF2 in autophagy by p62. A Crispr-based screen focused on finding novel negative regulators of NRF2 signaling ( 133 ) also identified a number of autophagy-related genes in human kidney HK2 cells. However, subsequent functional analyses demonstrated that changes in the phosphorylation of p-p62 do not necessarily induce NRF2 in HK2 cells, indicating that the autophagy-NRF2 loop can proceed in a p62-independent manner.…”
Section: Role Of Nrf2 In Cancermentioning
confidence: 99%
“…Other reports contradict the induction of NRF2 in autophagy by p62. A Crispr-based screen focused on finding novel negative regulators of NRF2 signaling ( 133 ) also identified a number of autophagy-related genes in human kidney HK2 cells. However, subsequent functional analyses demonstrated that changes in the phosphorylation of p-p62 do not necessarily induce NRF2 in HK2 cells, indicating that the autophagy-NRF2 loop can proceed in a p62-independent manner.…”
Section: Role Of Nrf2 In Cancermentioning
confidence: 99%
“…NRF2 has previously been linked to autophagy, and p62 sequesters and inhibits the NRF2-negative regulator, KEAP1 (Komatsu et al, 2010). Moreover, a recent genome-wide CRISPR screen showed that KO of a large subset of autophagy genes results in up-regulation of the NRF2 signaling pathway (Kerins et al, 2019). As a consequence of NRF2 up-regulation, the autophagy-deficient cells developed an increased sensitivity to pharmacological proteasome inhibitors, a phenotype that was exacerbated with NRF2 knockdown (Towers et al, 2019).…”
Section: Adaptation To Autophagy Inhibitionmentioning
confidence: 99%
“…Of note, restoring autophagy promoted spontaneous tumor development, suggesting that prolonged autophagy inhibition may select for additional stress-response pathways which accelerate disease progression when autophagy is restored. Recent studies demonstrate that overactivation of the oxidative stress response by the transcription factor Nrf2 is a dominant consequence of autophagy-related gene deletion in cancer cells ( Kerins et al, 2019 ; Towers et al, 2019 ). The association between autophagy inhibition and Nrf2 was reported even earlier, predominantly due to accumulation of p62 ( Komatsu et al, 2010 ; Inami et al, 2011 ; Ichimura et al, 2013 ).…”
Section: Adaptation Against Autophagy Inhibitionmentioning
confidence: 99%
“…Nonetheless, genetic models still comprise the large majority of evidence supporting more specific nodes of autophagy as targets. Beyond canonical members of the pathway, genetic phenotypic screens using engineered reporter cell lines have provided new insights for modulation of autophagic flux ( DeJesus et al, 2016 ; Morita et al, 2018 ; Kerins et al, 2019 ; Shoemaker et al, 2019 ). In addition, pharmacological screens with the same cellular tools have revealed inhibitors with new mechanisms of action.…”
Section: Hurdles To Successful Pharmacological Inhibition Of Autophagmentioning
confidence: 99%